BHARUGANO WUNA MUSEUM AS AN EFFORT TO PRESERVE AND REVITALIZE THE CULTURE OF THE MUNA COMMUNITY IN MUNA REGENCY - Susi Harnisa; Tama Maysuri; Siti Musa’adah; Gesia M. Urlialy (Kalyanamitra: Journal of Archaeological Resource Management, 2026)
A museum is one of the institutions that has an important role in preserving the cultural heritage of a community. The existence of a museum not only functions as a place to store historical objects but also as an information center, a learning medium, and a means of cultural recreation for the community. This study aims to understand the history of the establishment of the Bharugano Wuna Museum, the development of the Bharugano Wuna Museum, and its role in preserving the culture of the Muna community in Muna Regency, Southeast Sulawesi. This research uses a historical research method which includes the stages of heuristics, source criticism, interpretation, and historiography. Data sources were obtained through interviews with museum managers, direct observation at the research location, as well as documentation studies of various written sources related to the Muna museum and culture. The research results show that the Bharugano Wuna Museum was originally a traditional Muna house built in 2017 and was then converted into a museum in 2018. This museum plays an important role as a center for cultural information, a medium for learning history, a facility for preserving cultural heritage, as well as a cultural tourism attraction in Muna Regency. In addition, community participation in contributing to museum collections shows the collective awareness of the community in preserving and maintaining local culture. Thus, the existence of the Bharugano Wuna Museum becomes one of the strategic efforts in maintaining the cultural identity of the Muna people while introducing regional cultural heritage to the wider public. Keywords: Bharugano Wuna Museum; cultural preservation; Muna community